An Integrated Quality Education Management in the Perspective of the Qur’an Qs. As- Syu’ara’ Verses 181-183 in Tafsir Al-Misbah - Sa'dullah Assa'idi; Azizil Muchtar; Mashudi Mashudi (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
This research was aimed at revealing and understanding the principle of customer satisfaction of the integrated quality education management in the Qur’an QS As-Syu’ara’ Verses 181-183, and the implication of the integrated quality education management. This study used content analysis where qualitative approach was employed. Integrated quality management on education was analyzed its component by consulting the messages and guides in the Qur’an QS As-Syuara’ Verses 181-183 interpreted in the tafseer Almisbach authorized by Indonesian Islamic scholar Prof. Dr. Quraish Shihab. Results show that quality management in education root on the Islamic teaching that to practice a continued improvement in the entire life. The quality appears as a daily worship that should improve day by day. Al Misbach provides guidance and enlightens that education management is complete measure. Accordingly, you don’t become one of the members of the groups of people who hurts oneself because of harming others, but weigh for yourself and for others using an accurate scale, don’t hurt others concerning their rights by reducing the quality or the value of something, and don’t make the evil on earth by becoming destroyers in any form after repair is made by Allah or also by human beings. If you give something to humans, thus perfect the scale and don’t you reduce the weight by giving them less than it should be.